The Role for Exosomal microRNAs in Disruption of Regulatory T Cell Homeostasis in Multiple Sclerosis. (23rd March 2018) - Kimura, Kimitoshi; Hohjoh, Hirohiko; Yamamura, Takashi
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system, in which myelin and oligodendrocytes are the main targets recognized by inflammatory CD4 + T cells reactive to myelin peptides. Regulatory CD4 + T (Treg) cells normally keep homeostasis of the immune system by inhibiting detrimental effects of inflammatory T cells. However, Treg cells are reduced in patients with MS for unknown reason. This commentary highlights a novel function of circulating exosomes to inhibit the differentiation of Treg cells in MS. Our recent work has demonstrated that the circulating exosomes, a member of extracellular vesicles, of patients with MS exert this effect by transferring let-7i to naive CD4 + T cells. The transferred let-7i subsequently causes a decreased expression of insulin like growth factor 1 receptor (IGF1R) and transforming growth factor β receptor 1 (TGFBR1), leading to the inhibition of Treg cell differentiation. Thus, extrinsic microRNAs transferred by exosomes might have an active role in triggering autoimmune diseases. We hypothesize that extracellular vesicles including exosomes can be a communication tool between the gut microbiota and the host immune system. Further research in this area will expand the knowledge about the precise mechanism of autoimmune diseases and can lead to a new therapeutic approach.